Shifting Identity in Kurmali: A Preliminary Observation - Gautam, Bhim Lal; Sapkota, Sharada (Nepalese Linguistics, 2024)
This paper investigates patterns, reasons, and effects of language shift in the Kurmi community located at eastern and southern part of Jhapa. It provides a detailed picture of language use and attitudes in different activities like migration, marriage, the media, and so on. The data was gathered through interviews, Focus Group Discussions (FGDs) and survey questionnaire during March-June, 2024. Questionnaires were analyzed in Excel tools and the qualitative data were interpreted on various themes. This study realizes that the younger Kurmis do not speak this language in their daily life because of the influence of media, migration and globalization.